Integrin-Linked Kinase Expression Characterizes the Immunosuppressive Tumor Microenvironment in Colorectal Cancer and Regulates PD-L1 Expression and Immune Cell Cytotoxicity - Almasabi, Saleh; Boyd, Richard; Ahmed, Afsar U.; Williams, Bryan R. G. (Frontiers in Oncology, 2022)
Integrin-linked kinase (ILK) has been implicated as a molecular driver and mediator in both inflammation and tumorigenesis of the colon. Here, we show a correlation of ILK expression with the immunosuppressive tumor microenvironment (TME) and cancer prognosis. We also uncover a role for ILK in the regulation of programmed death-ligand 1 (PD-L1) expression. Interrogation of web-based data-mining platforms, showed upregulation of ILK expression in tumors and adjacent-non tumor tissue of CRC associated with poor survival and advanced stages. ILK expression was correlated with cancer-associated fibroblast (CAFs) and immune cell infiltration including CD4+ T cells, macrophages, neutrophils and dendritic cells (DCs). ILK expression was also significantly correlated with the expression of different cytokines and chemokines. Several markers and genes related to immunosuppressive cells including M2 macrophages, tumor-associated macrophages (TAMs) as well as regulatory T cells (Treg) and T cell exhaustion displayed positive correlation with ILK expression. ILK expression showed pronounced association with different important immune checkpoints including PD-L1. Deletion of the ILK gene in PD-L1 positive CRC cells lines using a doxycycline inducible CRISPR/Cas9, resulted in suppression of both the basal and IFNγ-induced PD-L1 expression via downregulating NF-κB p65. These findings suggest that ILK can be used as a biomarker for prognosis and immune cell infiltration in colon cancer. Moreover, ILK could provide a therapeutic target to prevent immune evasion mediated by the expression of PD-L1.